Allergen immunotherapy for allergic rhinoconjunctivitis: A systematic review and meta‐analysis. Issue 11 (14th July 2017) - Dhami, S.; Nurmatov, U.; Arasi, S.; Khan, T.; Asaria, M.; Zaman, H.; Agarwal, A.; Netuveli, G.; Roberts, G.; Pfaar, O.; Muraro, A.; Ansotegui, I. J.; et al.
Abstract: Background: The European Academy of Allergy and Clinical Immunology (EAACI) is in the process of developing Guidelines on Allergen Immunotherapy (AIT) for Allergic Rhinoconjunctivitis. To inform the development of clinical recommendations, we undertook a systematic review to assess the effectiveness, cost‐effectiveness, and safety of AIT in the management of allergic rhinoconjunctivitis. Methods: We searched nine international biomedical databases for published, in‐progress, and unpublished evidence. Studies were independently screened by two reviewers against predefined eligibility criteria and critically appraised using established instruments. Our primary outcomes of interest were symptom, medication, and combined symptom and medication scores. Secondary outcomes of interest included cost‐effectiveness and safety. Data were descriptively summarized and then quantitatively synthesized using random‐effects meta‐analyses. Results: We identified 5960 studies of which 160 studies satisfied our eligibility criteria. There was a substantial body of evidence demonstrating significant reductions in standardized mean differences (SMD) of symptom (SMD −0.53, 95% CI −0.63, −0.42), medication (SMD −0.37, 95% CI −0.49, −0.26), and combined symptom and medication (SMD −0.49, 95% CI −0.69, −0.30) scores while on treatment that were robust to prespecified sensitivity analyses. There was in comparison a more modest body of evidence on effectiveness post‐discontinuation of AIT, suggesting a benefit in relation to symptom scores. Conclusions: AIT is effective in improving symptom, medication, and combined symptom and medication scores in patients with allergic rhinoconjunctivitis while on treatment, and there is some evidence suggesting that these benefits are maintained in relation to symptom scores after discontinuation of therapy.